LEARNING STYLES AND MOBILE LEARNING USAGE BEHAVIORS OF GRADUATE STUDENTS IN UNIVERSITY IN CURBING PLASTIC POLLUTION - Chantana Viriyavejakul (My University, 2020)
Plastic waste pollution has already affected everything on earth, especially with frighteningly high amounts of waste plastic being found recently in un-inhabited places. Responsibility of reducing plastic use and waste is more dependent on highly
Keywords: Plastic pollution; Plastic Waste; Impact of Technology on Adolescents